A Study on the First Grade Students’ Understanding of Personal Pronouns in English Reading Texts at SMPN 1 Singingi - fanny laina tussifa; harum natasha (Indonesian Journal of Integrated English Language Teaching, 2021)
The problem of this research was to know how well the students’ of SMPN 1 Singingi in Understanding personal pronouns in a text at SMPN 1 Singingi is. The research was conducted at SPMN 1 Singingi from Februari 3rd to Februari 27th, 2021.  The population of this research  was 40 students of two classes and researcher took 20 students as the sample. This research was quantitaive- descriptive research. Researcher used fill-in-the-blank text test to collect the data. In analyzing the data, researcher collected and classified each item of the test and multiplied them by standardizing the scores that had been determined before. The next step was counted the percentage of the level of the students’ ability in using personal pronouns. From the research findings, researcher found that the test was gained 1545 from total scores of all the students who joined the test. The average of students' scores was 77.25 and the sum of the total scores was 85%. It means that most of the students did well on the test and understood personal pronouns in reading text.